Aplikasi Terapi Relaksasi Nafas Dalam terhadap Pengontrolan Marah dengan Pasien Gangguan Jiwa Resiko Perilaku Kekerasan di Wilayah Desa Maleber Kabupaten Cianjur - Biyan Tazqiyatus Sudia (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Violent behaviour is a condition in which a person performs actions that are physically harmful to themselves and others. Often also called tantrums where someone where someone is angry responds to a stressor with uncontrolled motor movements. The nursing intervention given is the deep breathing relaxation technique for controlling anger. The purpose of this application is to determine the effect of the application of deep breathing relaxation therapy in patients with risk problems for violent behavior in Maleber village, Cianjur district. The method used is total sampling, the sample taken is 1 respondent, namely patients at risk of violent behaviour. The data of this study were taken using interviews, observations, documentation studies of deep breathing relaxation therapy carried out for 3 times in 3 days effectively to control ongoing anger in patients at risk of violent behavior after taking action for 3 days of anger in patients at risk of violent behavior, Anger can be controlled